Novel Energetic Coordination Polymers Based on 1,5-Di(nitramino)tetrazole With High Oxygen Content and Outstanding Properties: Syntheses, Crystal Structures, and Detonation Properties - Li, Yanan; Yu, Tao; Zhang, Yiying; Hu, Jianjian; Chen, Tao; Wang, Yinglei; Xu, Kangzhen (Frontiers in Chemistry, 2019)
In this study, a series of novel 1,5-di(nitramino)tetrazole (DNAT)–based bimetallic energetic coordination polymers, MK2(DNAT)2·4H2O [M = Fe, Cu, Ni, Co, and Zn], were designed and synthesized in a simple and convenient self-assembly synthetic process. The obtained compounds were fully characterized by IR spectroscopy, multinuclear NMR spectroscopy, elemental analysis, and differential scanning calorimetry (DSC). Additionally, the structures of target compounds were confirmed by single-crystal X-ray diffraction. Based on the room-temperature X-ray densities (2.095 – 2.138 g cm-3) and the calculated (CBS–QB3) heats of formation (-41.3 – 170.5 kJ mol-1), the detonation properties such as detonation velocities (8147.0 – 8478.4 m s-1) and detonation pressures (29.7 – 32.8 GPa) were computed using the EXPLO5 v6.04 program. Their excellent energetic properties indicated that they could serve as promising “green” primary explosives for replacement of lead azide (LA).